Texture analysis in radiology: Does the emperor have no clothes? - Summers, Ronald (Abdominal Radiology, 2017)
Texture analysis is more and more frequently used in radiology research. Is this a new technology, and if not, what has changed? Is texture analysis the great diagnostic and prognostic tool we have been searching for in radiology? This commentary answers these questions and places texture analysis into its proper perspective.